Distribution and phenology of Bomarea (Alstroemeriaceae)in the relict forests of northwestern Peru - Hofreiter, Anton (2005)
The distribution, phenology and diversity of Bomarea in the relict forests of northwestern Peru is discussed and compared to the cloud forests of the eastern slope of the Andes. Most species of subgenus Bomarea and all species of subgenus Sphaerine have southernmost distribution limit in the Cordillera Occidental in the relict forests of NW Peru. The phenology of some species of Bomarea species differs between the relict forests and the eastern slopes of the Andes, whereas no differences are observed in Sphaerine.